Intellectual Capital Disclosure and Firm Performance: An Empirical Analysis Through Integrated Reporting - Filippo Vitolla; Nicola Raimo; Michele Rubino (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
The purpose of this document is to empirically examine the impact of intellectual capital disclosure quality in the integrated reports on firm performance. The empirical research is based on a sample of 45 integrated reports. The results confirm our hypothesis that establish the existence of a significant and positive association between the intellectual disclosure quality and the firm performance. The results of this document are of considerable importance to policy makers and managers. In fact, an understanding of the benefits of intellectual capital disclosure quality, helps policy makers to assess the costs and benefits of disclosure. As far as managers are concerned, this study clearly shows that intellectual capital disclosure is a means to improve firm performance. This study is one of the first to provide evidence of the positive association between intellectual capital disclosure quality and firm performance in the context of integrated reporting.
Keywords: 650; intellectual capital; integrated reporting; firm performance